Investigating Small-Scale Air–Sea Exchange Processes via Thermography - Kunz, Jakob; Jähne, Bernd (Frontiers in Mechanical Engineering, 2018)
The exchange of trace gases such as carbon dioxide or methane between the atmosphere and the ocean plays a key role for the climate system. However, the investigation of air-sea gas exchange rates lacks fast and accurate measurement techniques that can be used in field campaigns, e.g. onboard a ship on the ocean. A promising way to overcome this deficiency is to use heat as a proxy tracer for gas transfer. Heat transfer rates across the aqueous boundary layer of the air-water interface can be measured via thermography with unprecedented temporal and spatial resolution in the order of minutes and meters, respectively. Either passive or active measurement schemes can be applied. Passive approaches rely on temperature differences across the water surface that are caused naturally by radiative and evaporative cooling of the water surface. Active measurement schemes force an artificial heat flux through the aqueous boundary layer by means of heating a patch at the water surface with an appropriate heat source, such as a $CO_2$ laser. For the active measurement approach the choice of the excitation signal is crucial. It is beneficial to apply periodic heat flux densities with different excitation frequencies. In this way, the air-water interface can be probed for its response in terms of temperature amplitude and phase shift between excitation signal and temperature response. This concept from linear system theory is also well established in the field of non-destructive material testing, where it is known as lock-in thermography. This article gives a short introduction into air-sea gas exchange, before it presents an overview of different thermographic measurement techniques used in wind-wave facilities and at sea from their early implementations. The article closes with a novel multifrequency excitation scheme for even faster measurements.